Effectiveness of ureteroscopy among the youngest patients: One centre's experience in an endemic region in Turkey. Issue 1 (February 2017) - Utanğaç, Mehmet Mazhar; Dağgülli, Mansur; Dede, Onur; Sancaktutar, Ahmet Ali; Bozkurt, Yaşar
Summary: Background: In recent years, the incidence of urinary stone disease reportedly has been increasing. The use of shockwave lithotripsy has seen low success rates, the inefficacy of a single session, and the need for general anaesthesia in children; additionally, children are exposed to radiation. These suboptimal treatment conditions have all led to ureteroscopy (URS) becoming the treatment method of choice for paediatric ureter stones. The aim of this study is to examine the effectiveness of 4.5-Fr URS when used on children younger than 1 year of age. Patients and methods: The operation results of 34 patients (12 girls and 22 boys) who had undergone intervention for ureter stones at our clinic were retrospectively evaluated. For URS, a 4.5-Fr semi-rigid ureteroscope was used; a Holmium:YAG laser machine was used as a lithotripter. Result: The mean patient age was 9.6 months (range 4–12 months) (Table). The mean stone surface area was 25.39 mm 2 (range 11.84–84.78 mm 2 ). In six cases, a ureteral catheter was inserted, because of minimal oedema in the ureters; in nine cases, a Double J (DJ) stent was inserted. The mean operation time was 45.3 min (range 22–87 min). In the first week of control with urinary ultrasonography and kidney–ureter and bladder radiograph, a stone-free condition was determined in 28 (82.3%) patients. In two cases—in which sufficient fragmentation could not be achieved, because of minimal bleeding during operation—during the exertion of a DJ stent, another URS was performed. In the first postoperative month, a stone-free condition was established in 32 (94.1%) patients. The mean hospital stay period was 28.6 h (range 12–72 h). There were seven cases (20.5%) with Clavien II–III complications. Conclusion: Use of a ureteroscope is safe and effective with paediatric patients: we found that a 4.5-Fr ureteroscope can be safely used on children under 1 year of age. We therefore consider a 4.5-Fr ureteroscopic instrument to be an appropriate tool for treating URS in children within this age range. Table The data work. Age 9.6 months (4–12) Stone surface area (mm 2 ) 25.39 (11.84–84.78) Operation time 45.3 min (22–87) Stoneless First week 28 patients (82.3%) First month 32 patients (94.1%) Total complications 7 patients (20, 5%)